Impact Of Various Biodiesel And Partially Hydrogenated Biodiesel Mixtures On Torque, Power, And Specific Fuel Consumption: An Experimental Study With Mathematical Modelling - I Ketut Gede Wirawan; I Nyoman Prayana Trisna (Scientific Contributions Oil and Gas, 2024)
The widespread reliance on diesel fuel for transportation and industrial applications necessitates exploring better alternatives. Biodiesel, either alone or in combination with partially hydrogenated biodiesel, presents a potential substitute for conventional diesel fuel. This research investigates the effects of incorporating biodiesel or partially hydrogenated biodiesel into diesel fuel on torque, power, and specific fuel consumption (SFC). The experiments incorporated seven mixtures of diesel fuel, varying from 100% diesel fuel to only 70% diesel fuel. The findings indicate that both biodiesel and partially hydrogenated biodiesel improve power, torque, and SFC compared to conventional diesel fuel, across various ratios and engine rotation. Optimal performance of these biodiesel blends is achieved around 2000 rpm. Additionally, the study developed mathematical models to predict torque and power, which were optimized for use at engine speeds of 2000 rpm and 4000 rpm, with biodiesel concentrations ranging from 10% to 30% in the fuel mixture.